2021
DOI: 10.1007/s11356-021-13873-y
|View full text |Cite
|
Sign up to set email alerts
|

Does improvement in the environmental sustainability rating help to reduce the COVID-19 cases? Controlling financial development, price level and carbon damages

Abstract: The study’s objective is to evaluate the impact of environmental sustainability rating, financial development, changes in the price level and carbon damages on the new COVID-19 cases in a cross-sectional panel of 17 countries. The study developed two broad models to analyse the relationship between the stated factors at the current level and forecast level. The results show that improvement in the environmental sustainability rating and financial efficiency reduces the COVID-19 cases, while continued economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
3
6
1
Order By: Relevance
“…Our findings are similar to those reported by Anser et al ( 2021 ). The variables for the environmental performance COEM and FFC with coefficients of 0.0039 and 0.2133 negatively impact communicable diseases like COVID-19 and the earlier variants of CDs.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are similar to those reported by Anser et al ( 2021 ). The variables for the environmental performance COEM and FFC with coefficients of 0.0039 and 0.2133 negatively impact communicable diseases like COVID-19 and the earlier variants of CDs.…”
Section: Resultssupporting
confidence: 94%
“…Resultantly, the lockdowns in the economy and shutdowns in industries caused a loss in their regular pay and payments for healthcare treatments. Thirdly, while the personal earnings and savings appear to be the first line of defense during the shocks of CDs, the OECD residents may well employ credit financing and resort to borrowings offered by improved levels of financial development, as reported by Anser et al ( 2021 ). In the context of the above discussion, among other SDGs, the importance of appropriate public and private investments is highly recommended for transition to a green economy with high levels of environmental sustainability as well as general public health, as was also suggested by Sachs et al ( 2019 ) and Le et al ( 2020 ).…”
Section: Resultsmentioning
confidence: 91%
“…On the other hand, it increases untreated healthcare wastes, which affect the sustainability principles. Further, the number of studies confirmed the estimated results of improving environmental sustainability ratings in the wake of COVID-19 cases and natural resources (see Anser et al 2021b;Quatrini 2021;Boston 2020).…”
Section: Resultssupporting
confidence: 60%
“…The earlier studies mainly included different environmental pollution in the COVID-19 framework (see Pei et al 2020;Zhu et al 2020;Frontera et al 2020;Jiang et al 2020) while ignored the more comprehensive policy variable related to ESR during the pandemic recession. This variable is essential, as it described the country's overall rating towards achieving environmental sustainability from a policy perspective (Anser et al 2021b). Furthermore, the commodity-producing sector is also negatively affected by the high COVID-19 cases due to adopting strict lockdown measures and maintaining social distancing in the mining, which affects their working conditions and livelihood to escape poverty.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 16 ] identified critical factors associated with COVID-19 cases, death, and case fatality rates by using the logistic regression model. Anser et al [ 17 ] developed two broad models to evaluate the impact of environmental sustainability ratings, financial development, and carbon damage on the new COVID-19 cases in a cross-sectional panel of 17 countries. Abdel Hafez and Hamdan [ 18 ] used three artificial neural network (feed-forward, NARX, and Elman network [ 19 ]) methods to evaluate the relationship between weather variables and COVID-19 cases.…”
Section: Introductionmentioning
confidence: 99%